2003
DOI: 10.1177/0731684403022004842
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Fracture Resistance Analysis of Polymer Composites Based on the Energy Expended on Damage Formation

Abstract: Analysis of the fatigue crack propagation behavior of filled polytetrafluoroethylene (PTFE) composites using the energy expended on damage formation was performed. A 25% chopped glass fiber filled PTFE with a commercial name of Rulon LR and a 25% polymer particle filled PTFE (Rulon J) were chosen as candidate materials for the study. Fatigue crack propagation (FCP) tests were performed using both unnotched and single edge notched (SEN) specimens under tension-tension load control condition. The notched specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Hahn and Kim [17] used the width of the hysteresis loop, measured intermittently, as a measure of damage. Aglan et al related crack propagation with hysteresis, an approach that requires locating and identifying a major crack in the material, a difficult problem in composites since damage zones may contain several cracks [36,37]. Identifying the critical crack in a composite laminate is not trivial.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hahn and Kim [17] used the width of the hysteresis loop, measured intermittently, as a measure of damage. Aglan et al related crack propagation with hysteresis, an approach that requires locating and identifying a major crack in the material, a difficult problem in composites since damage zones may contain several cracks [36,37]. Identifying the critical crack in a composite laminate is not trivial.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Aglan et al used hysteresis area along with crack propagation measurements to calculate a specific energy of damage from cyclic energy dissipation [36,37]. Hahn and Kim [17] plotted the horizontal width of the hysteresis loop as a function of life, while Sarkani et al [38] employed the center of gravity of the loop which was found to increase linearly with fatigue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Sutton et al [36] investigated the fatigue behavior of PI-based composites using the concept of damage formation. This theory considers a fatigue crack and the surrounding processing zone at its tip as a thermodynamic object, where the material damage degree is associated with the system entropy and the energy dissipation rate for the initiation of a new surface.…”
Section: Introductionmentioning
confidence: 99%
“…The energy dissipated into damage formation is considered as the indentation penetration driving force. A materials parameter, the specific energy of damage is used as the contact damage tolerance criterion as previously introduced for some materials in [41][42][43][44][45][46]. Correlation between the contact damage tolerance and the microstructure of the material is made.…”
Section: Contact Damage Propagation Stage: Macroscale Approachmentioning
confidence: 99%